Thermo-hydro-mechanical coupling mechanisms and sensitivity analysis of abandoned mine thermal energy storage systems - Liyuan LIU; Yaohui LI; Tao WANG; Tongbin ZHAO; Qiang KOU; Zerui MI; Le ZHANG (工程科学学报)
Given the extensive abandonment of mines in China, the abundant non-mineral resources exposed in derelict mine workings pose challenges in addressing idle mine risks while also presenting opportunities for improving energy infrastructure. By fully utilizing the underground spaces and geothermal resources of abandoned mines, they can be transformed into efficient abandoned mine thermal energy storage (MTES) systems. Through the rational exploitation of deep mine geothermal environments, this approach enables seasonal storage of surplus thermal energy from wind/solar power and industrial waste heat during summer. Subsequently, it enables heat extraction for winter heating services, thereby achieving significant energy conservation and enhanced utilization efficiency. Mine water thermal resources are attracting strong academic interest due to their abundant natural reservoirs and favorable geothermal environments. Globally, the geothermal potential of mine water has gained widespread recognition. The formation of artificial pseudo-aquifers through mine void networks allows contained hydrothermal resources to demonstrate substantial heat supply potential to surrounding areas. Thermal energy recovery from mine water can yield several times more energy than the electrical power required for pumping operations. Consequently, numerous thermal utilization projects focusing on abandoned mine water have entered research phases, particularly in European countries facing energy crises that urgently require improved energy efficiency or novel energy sources, to optimize existing supply structures. Compared with direct utilization of mine water thermal resources, seasonal thermal energy storage utilizing mine environments appears more attractive. In this study, a multiphysics coupled mechanical model is established for MTES systems based on porous media elastic mechanics theory, incorporating thermal conduction and convection effects in water–rock interactions while neglecting seepage heat transfer in rock masses. Numerical simulations and evaluations are conducted to assess the long-term operational performance of this system. Furthermore, the Distance-based Generalized Sensitivity Analysis (DGSA) method is employed to thoroughly investigate parameter sensitivity in the MTES model. A three-dimensional thermo-hydro-mechanical (THM) coupled numerical model is developed to calculate the coupled effects over a decade of system operation and analyze heat transfer processes along with stress variation patterns in the roadway’s surrounding rock. Results indicate that the MTES system effectively utilizes geothermal environments for high-efficiency storage of waste heat, achieving a residual temperature of 35.5 ℃ (44.4% retention rate) during the first year following the injection of 80 ℃ water, with winter extraction temperatures progressively increasing annually. The tenth-year output temperature shows an increase of 10.3 ℃ compared to the first year, maintaining only 6–7 ℃ fluctuations throughout winter heating periods. Once the MTES system stabilizes, output temperatures range from 52 ℃ to 58 ℃, with operational efficiency continuously optimizing over time, ensuring long-term performance sustainability. With increasing operational cycles, the system’s thermal recovery efficiency gradually rises, while annual growth rates decrease with accumulated cycles, showing a 10% improvement within two years. By the fifth cycle, MTES achieves 50.4% thermal recovery efficiency, with the third cycle reaching 46.5%. Stress analysis further demonstrates that thermal storage operations maintain roadway stability, confirming the feasibility and safety of MTES implementation. Using the DGSA methodology, sensitivity quantification is performed by classifying model responses calculated from stochastic sample deviations. Sensitivity results identify summer injection temperature and injection rate as the most critical parameters affecting system efficiency, followed by roadway temperature characteristics. This research provides crucial theoretical support and practical guidance for field testing and large-scale engineering applications of abandoned mine thermal storage systems, offering scientifically reliable technical recommendations for practical testing and engineering implementation. The findings substantially contribute to addressing energy structure optimization challenges through the sustainable repurposing of abandoned mine resources.